Kontrol Perilaku Ibu Rumah Tangga Terhadap Penggunaan Tas Belanja untuk Mengurangi Penggunaan Kantong Plastik Terhadap Lingkungan Sekitar - Deviana Melati (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The environmental pollution that occurs is increasingly creating awareness on the part of consumers. Wrong One cause of environmental pollution is the use of plastic bags. Use of pockets Plastics that are not environmentally friendly cause environmental damage. Therefore, it is necessary there is a change in the use of inorganic plastic bags to environmentally friendly shopping bags. Changing the use of environmentally friendly shopping bags can reduce the impact of pollution Environment: The aim of this research is to investigate changes in green bags or ecobags Use environmentally friendly shopping bags instead of plastic bags. Environmentally friendly tote bags made from canvas or various types of fabric with designs that have added value and can be folded into a pocket bag, with the addition of batik cloth elements as a medium for preserving Indonesian culture can create added value for both the user and the supplier himself. This idea emerged because of the accumulation of rubbish which is always increasing every day in every part of the world. In Indonesia itself, plastic waste is in the second highest position after food waste. This is based on data in the National Waste Management Information System (SIPSN) in 2021, approximately 15.7% of waste in Indonesia is in the form of single-use plastic. Data from the Indonesian Central Statistics Agency (BPS) in 2018 shows the fact that Indonesia is the second largest contributor of plastic waste in the world. People consume a lot of instant food with plastic packaging, and a lot of it people who have the habit of using plastic bags when carrying out Shopping transactions are the cause of the accumulation of plastic waste in Indonesia.